Prognostic value of baseline genetic features and newly identified TP53 mutations in advanced breast cancer. Issue 20 (15th August 2022) - Zhang, Lanxin; Sun, Siwen; Zhao, Xiaotian; Liu, Jingwen; Xu, Yang; Xu, Lingzhi; Song, Chen; Li, Na; Yu, Jing; Zhao, Shanshan; Yu, Peiyao; Fang, Fengqi; et al.
Abstract : Approximately 30% of breast cancer (BC) patients suffer from disease relapse after definitive treatment. Monitoring BC at baseline and disease progression using comprehensive genomic profiling would facilitate the prediction of prognosis. We retrospectively studied 101 BC patients ultimately experiencing relapse and/or metastases. The baseline and circulating tumor DNA‐monitoring cohorts included patients with baseline tumor tissue and serial plasma samples, respectively. Samples were analyzed with targeted next‐generation sequencing of 425 cancer‐relevant genes. Of 35 patients in the baseline cohort, patients with TP53 mutations ( P  < 0.01), or CTCF/GNAS mutations ( P  < 0.01) displayed inferior disease‐free survival, and patients harboring TP53 ( P  = 0.06) or NOTCH1 ( P  = 0.06) mutations showed relatively poor overall survival (OS), compared to patients with wild‐type counterparts. Of the 59 patients with serial plasma samples, 11 patients who were newly detected with TP53 mutations had worse OS than patients whose TP53 mutational status remained negative ( P  < 0.01). These results indicate that an inferior prognosis of advanced breast cancer was potentially associated with baseline TP53, CTCF, and NOTCH1 alterations. Newly identified TP53 mutations after relapse and/or metastasis was another potential prognostic biomarker of poor prognosis. Abstract : This study provided insights into the prognostic value of genetic features obtained at baseline and/or during dynamic monitoring advanced breast cancer (ABC). Baseline altered TP53, CTCF, GNAS, and NOTCH1 genes were negative prognostic factors, and the evolutionary pattern of TP53 mutation during ABC treatment could potentially serve as a prognostic factor for recurrent patients.